MOTILIN-IMMUNOREACTIVE CELLS IN THE DUODENUM, PYLORIC STOMACH AND PANCREAS OF CAIMANS (CAIMAN-LATIROSTRIS AND CAIMAN-CROCODILUS, ALLIGATORINAE) - A FURTHER COMPARISON USING REGION-SPECIFIC MOTILIN ANTISERA - Yamada, J.; Rodrigues, MAM; Kitamura, N.; Pai, V. D.; Yamashita, T.; Motizuki, T.; Yanaihara, N. (Japan Soc Histol Documentation Niigata Univ Medical School, 1991)
Motilin-immunoreactive cells in the duodenum, pyloric stomach and pancreas of Caiman latirostris and Caiman crocodilus were investigated using region specific antisera for porcine and canine motilin molecules. Motilin-immunoreactive cells were found in the duodenum, pyloric stomach and pancreas of both caiman species. These cells were primarily open-type endocrine ones in the epithelium of the duodenum and pyloric stomach. Motilin-immunoreactive cells were observed in both the exocrine and endocrine portions of the pancreas, and frequently exhibited one or more cytoplasmic processes of variable length. Since motilin-immunoreactive cells do not cross-react with serotonin or any of the other pancreatic and gut hormones, they are considered to be cell type independent from any of the other known pancreatic or gut endocrine cells. The molecular similarity between caiman motilin and porcine and canine motilins and the heterogeneity of the motilin molecule in the caiman digestive system is discussed.